2016
DOI: 10.1039/c6nr00368k
|View full text |Cite
|
Sign up to set email alerts
|

Affinity capture using peptide-functionalized magnetic nanoparticles to target Staphylococcus aureus

Abstract: Staphylococcus aureus, a commonly found pathogen, can cause food poisoning and infections. Thus, it is necessary to develop analytical methods for the rapid screening of S. aureus in suspicious samples. Magnetic nanoparticles (MNPs) are widely used as affinity probes to selectively enrich target species from complex samples because of their high specific surface area and magnetic properties. The MNP surface should be functionalized to have the capability to target specific species. We herein propose a straight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…As reported, Hussain et al (2018) connected vancomycin-loaded nanoparticles with the cyclic 9-amino-acid peptide CARGGLKSC (CARG) which could specifically bind to S. aureus , realizing more effective suppression of staphylococcal infections in vivo than untargeted treatment ( Figure 3B ). Moreover, magnetic nanoparticles (MNPs) could also serve as affinity probes to selectively enrich S. aureus with peptide HHHHHHDEEGLFVD (D) due to special properties ( Kuo et al, 2016 ). On this basis, improvements lie in the addition of outer package to maintain long effects.…”
Section: Nanomaterial-based Targeted Therapymentioning
confidence: 99%
“…As reported, Hussain et al (2018) connected vancomycin-loaded nanoparticles with the cyclic 9-amino-acid peptide CARGGLKSC (CARG) which could specifically bind to S. aureus , realizing more effective suppression of staphylococcal infections in vivo than untargeted treatment ( Figure 3B ). Moreover, magnetic nanoparticles (MNPs) could also serve as affinity probes to selectively enrich S. aureus with peptide HHHHHHDEEGLFVD (D) due to special properties ( Kuo et al, 2016 ). On this basis, improvements lie in the addition of outer package to maintain long effects.…”
Section: Nanomaterial-based Targeted Therapymentioning
confidence: 99%
“…Jo et al used nano-MNPs for catching free cancer cells [ 21 ]. Kuo et al [ 22 ] reported biofunctional MNPs for pathogen separation and concentration. MNPs are also utilized for purifying target bacteria and increasing their count to allow the easy bacterial identification [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of aptamer-based capture/enrichment and MS analysis of microorganisms takes advantage of the selectivity of both techniques and should enhance the accuracy of microbial identification. A peptide aptamer that recognizes both SA and MRSA has been immobilized on gold nanoparticles to capture the bacteria prior to surface-assisted laser desorption ionization-MS analysis [ 38 , 39 ]. The present study aims to develop an affinity mass spectrometric method for selective analysis of MRSA.…”
Section: Introductionmentioning
confidence: 99%